Fast Isolation of Flavonoids from the Endemic Species Nolana ramosissima I.M. Johnst and Its Endothelium-Independent Relaxation Effect in Rat Aorta - Cifuentes, Fredi (Molecules, 2020)
The infusion of the desertic plant Nolana ramosissima I.M. Johnst showed vascular smooth muscle relaxation in rat aorta and the presence of several phenolic compounds, which were detected by high resolution UHPLC-Orbitrap-HESI-MS. In addition, five flavonoids were rapidly isolated from a methanolic extract using high-performance counter-current chromatography (HPCCC). The N. ramosissima extract showed endothelium-independent relaxation effect in rat aorta. Sixty-one compounds were detected in the infusion, mainly glycosylated flavonoids, flavanones and several oxylipins, suggesting that a synergistic effect between the compounds in the extracts could be responsible for the relaxation activity. Vascular activity experiments were done in isolated organ bath. In rat aorta, a nitric oxide inhibitor did not prevent the relaxation effects of the extract; however, a selective guanylyl cyclase inhibitor partially blunted this effect. The compound 5,3′-dihydroxy-4′7-dimethoxyflavone presented higher relaxation effect than 100 μg/mL of N. ramosissima extract. The extract and the isolated metabolites from N. ramosissima can show relaxation effects on rat aorta by a mechanism that is independent of the endothelium.